Cancer in the pilonidal sinus: Report of two cases, and review of the literature - Kamaid Toth, Emil; Olivera, Eduardo; Giannini, Gabriel; Pereyra, Jorge; Juri, Héctor; Bordes, Daniel; Deneo, Hugo; Kamaid Buchdid, Emil (Cirugía del Uruguay, 1996)
The authors present two cases of carcinoma deve/oped in a py/onidal cyst; as it is an extreme/y rare disease and as no references were found in national literature, the authors analyze treatment features, evolution, and make a bibliographical review on the subject.